A CRISPR‐Based Selective Gene Inhibition Method Reveals Dynamic Features of a Cell Nucleus Nanobody Related to the Disease Myotonic Dystrophy. Issue 9 (17th May 2018) - Ma, Hanhui; Reyes‐Gutierrez, Pablo; Pederson, Thoru
Abstract: A major form of the severe pediatric muscle disease myotonic dystrophy is caused by a CTG repeat expansion in the gene ( dmpk ) for the enzyme DM protein kinase 1. As a consequence, this mutant allele produces aberrant transcripts that have elongated tracts of CUG repeats. These RNAs appear to stall within the cell nucleus, congressing in small, discrete bodies situated away from their site of gene transcription. Here, clustered regularly interspaced short palindromic repeats (CRISPR)‐based approach is deployed that reveals that these nuclear nanobodies are not static structures. When the transcription of the dmpk gene is halted by a targeted CRISPR‐based inhibition method, the preexisting transcripts delocalize from the nuclear bodies, showing that they are continuously trafficking through and are not stalled there in an accretion mode. This report is an example of how a novel method can address a nanoscale dimension of molecular cell biology in the nucleus, one with direct medical relevance. Abstract : A frequent goal in research on gene expression is to selectively inhibit the transcription of a particular gene . A method is introduced based on loading onto the desired gene an array of clustered regularly interspaced short palindromic repeats (CRISPR) machinery envisioned to roadblock progression of RNA polymerase. This new method for a gene involved in the pathogenesis of the disease myotonic dystrophy is involved.